Hubungan riwayat kehamilan dan asupan energi dengan kejadian anemia pada ibu hamil - Santri Pertiwi; Frida Arfah (Nur Science Institute, 2024)
Anemia is a condition in which a pregnant woman is iron-deficient or has a hemoglobin level ≤ 11 g/dL. The third trimester is the final stage of pregnancy (29–40 weeks), during which fetal growth continues, and the body prepares for delivery. This study aimed to examine the relationship between pregnancy history and energy intake and the incidence of anemia among pregnant women. An analytical survey with a cross-sectional design was used, and the chi-square test was applied. The study was conducted in the service area of the Johan Pahlawan Public Health Centre (Puskesmas Johan Pahlawan) from October to December 2023. The study population included 32 pregnant women, and a total sampling was used. The results showed no association between pregnancy history and anemia risk; however, energy intake was significantly associated with anemia risk among pregnant women in the Johan Pahlawan Public Health Centre service area, West Aceh Regency. To reduce anemia prevalence, healthcare workers are encouraged to provide pregnancy-related information to improve pregnant women's knowledge of anemia and to engage village health cadres in delivering pregnancy health education.